Southward subduction of the Mongolia–Okhostk Ocean: Insights from Early–Middle Triassic intrusive rocks from the Jiawula–Tsagenbulagen area in NE China. (22nd February 2019) - Dai, Meng; Yan, Guangsheng; Liu, Cui; Deng, Jinfu; Li, Yongsheng; Jia, Wenbin; Lai, Chun‐Kit
Abstract : New zircon U–Pb age data, Hf isotopes, whole‐rock major and trace elements, and Sr–Nd isotopic data for Early–Middle Triassic intrusive rocks from the Jiawula and Tsagenbulagen area in the southern part of the Erguna Massif provide valuable constraints on the southward subduction of the Mongolia–Okhostk Ocean lithosphere. The Jiawula–Tsagenbulagen granitoids mainly consist of granodiorite, quartz monzonite, and biotite granite. These granitoids, long believed to be mainly Late Jurassic–Early Cretaceous (ca. 150–139 Ma) and minor Permian (ca. 278 Ma and 254–253 Ma), are newly found to contain a latest Early Triassic to Middle Triassic generation (zircon U–Pb age: ca. 248–244 Ma). Geochemically, the Early to Middle Triassic granitoids are characterized by high SiO2 (74–77 wt.%) and Al2 O3 (12.2–15.95 wt.%), low Mg # values (12.98–37.32), and variable Na2 O/K2 O ratios (0.62–1.75). They are metaluminous to peraluminous and belong to the high‐K calc‐alkaline series. Moreover, they show enrichment in light rare earth elements and large‐ion lithophile elements and depletion in heavy rare earth elements and high‐field‐strength elements (e.g., Nb, Ta, and Ti). They have an increased amount of SiO2 /Al2 O3 but lower V/Th ratios and negative correlations between V/Th and SiO2 /Al2 O3 ratios, indicating that the magmas experienced various degrees of biotite and/or plagioclase fractional crystallization. Their whole‐rock εNd (t) and zircon εHf (t) values ranged from +1.07 to +4.15 and from +0.5 to +2.9, respectively, indicating that the primary magmas were probably generated by partial melting of juvenile crustal material with the help of mantle‐derived mafic magmas. These magmas subsequently underwent fractional crystallization, magma mixing, and a small amount of crustal contamination during their emplacement. The geochemical characteristics of these Early–Middle Triassic intrusive rocks have affinities with intrusive rocks from active continental margin settings. Therefore, we conclude that the Early–Middle Triassic magmatism in the Erguna Massif was generated within an Andean‐type arc setting related to the southwards subduction of the Mongol–Okhotsk oceanic plate beneath the Erguna Massif. We summarized previous age data of the Early to Late Triassic magmatic rocks from Erguna and Central Mongolia and identified arc setting granites and post‐orogenic granites. Thus, a tectonic evolutionary model was proposed for the geological observations in the Erguna and Central Mongolia massifs, involving the Triassic continuous southward subduction in the Erguna Massif and the Late Triassic slab‐rollback and back‐arc basin extension in the south‐eastern Central Mongolia Massif.